IMAGING OF NORMAL PRESSURE HYDROCEPHALUS - Nazwar, Tommy Alfandy; Bal'afif, Farhad; Wardhana, Donny Wisnu; Yueniwati, Yuyun; Pradana, Wisniardhy (Journal Of Cardiovascular, Neurovascular & Stroke, 2022)
Normal pressure hydrocephalus (NPH) is hydrocephalus without an increase in intracranial pressure. The term Idiopathic Normal Pressure Hydrocephalus (INPH) has been used to describe individuals presenting with ventriculomegaly of unexplained etiology, accompanied by the classic triad of symptoms (gait disturbance, urinary incontinence, and dementia). CT-scan is more practical, cheaper, widely available, and can assess the anatomical condition of the brain and ventricles, but MRI is the best modality and superior to CT. It can assess the anatomic conditions better, changes in white matter, and the presence of flow-void sign. Radiological signs of INPH are the presence of ventriculomegaly with Evan's index > 0.3, z-EI > 0.42, the presence of DESH (Disproportionately Enlarged Subarachnoid Space Hydrocephalus), cingulate sign, callosal angle <90°